Karakteristik Reservoir Panas Bumi Berdasarkan Analisis Kimia Fisik Fluida Area Bolaang Mongondow Timur - Bujung, Cyrke A.N.; Dungus, Ferdy; Yasin, Kartika Constantia (Universitas Negeri Manado, 2020)
ABSTRACT Geothermal is energy from the result of heat transfer by conduction or convection. Manifestations in the form of warm soil, steamy soil and hot springs are geothermal energy that reaches the surface. The geothermal system of the Bolaang Mongondow Timur area is controlled by the large caldera structure of Mount Ambang and several fault directions that control the appearance of surface manifestations in the form of solfatara and hot springs. However, until now the geothermal potential has not yet been developed. Therefore, researchers are interested in exploring the geothermal system of the East Bolaang Mongonow area to introduce and increase knowledge about the characteristics of geothermal reservoirs. Based on geothermal field fluid data and fluid content data manifestation of the East Bolaang Mongondow area using geochemical methods (Geothermometer SiO2, Na-K and Na-K-Ca) as well as physical chemical analysis of the fluid shows that the geothermal area of the East Bolaang Mongondow area has a bicarbonate fluid type and sulfuric acid, with the type of reservoir dominated by steam and reservoir temperatures using the Geothermometer equation Na-K (Giggenbach) is 317.12 ° C. Keywodrs : Fault, Manifestation, Type Of Fluid, Type of Reservoir, Temperature .